The contribution of moral injury to Israeli teachers’ mental health difficulties: the mediating role of shame and guilt - Kaplan, Nir; Zerach, Gadi; Levi-Belz, Yossi (Frontiers in Psychiatry, 2025)
IntroductionExposure to potentially morally injurious events (PMIEs) has been found to contribute to mental health difficulties (MHD). However, research on PMIE exposure and its consequences among teachers is scant. In this study, we aimed to narrow this gap by examining the associations between teachers’ exposure to PMIEs and measures of depression, anxiety, burnout, and intention to leave the profession. Furthermore, we examined the mediating role of expressions of moral injury (i.e., shame and guilt) in these associations.MethodA sample of 253 Israeli teachers (186 female, 73%) aged 23-66 (Mage = 44, SD = 10.36) completed validated self-report questionnaires assessing the study variables.ResultsThe findings demonstrated that exposure to PMIEs contributed significantly to depression, anxiety, burnout, and intention to leave the profession. Through structural equation model analysis, we found that expressions of moral injury mediated the association between PMIEs and MHD.DiscussionThis study underscores the need to address moral injury among teachers as an essential factor for maintaining their mental health, as well as the overall sustainability of the educational system. Early screening and interventions are needed to identify and treat teachers at risk for MHD stemming from moral injury.